2008
DOI: 10.1007/s12033-008-9039-6
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Profiling of Gene Expression Changes in a PACE-Transfected CHO DUKX Cell Line Secreting High Levels of rhBMP-2

Abstract: Chinese hamster ovary (CHO) cells are widely used in the biopharmaceutical industry for the production of recombinant human proteins including complex polypeptides such as recombinant human bone morphogenic protein 2 (rhBMP-2). Large-scale manufacture of rhBMP-2 has associated production difficulties resulting from incomplete processing of the recombinant human protein due to insufficient endogenous levels of the paired basic amino acid cleaving enzyme (PACE) in CHO. In order to resolve this issue, CHO DUKX ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 65 publications
4
33
0
Order By: Relevance
“…Indeed, as recently stated by Clarke and Lee (2014), the CHO community is currently generating 'omics data at an ever-increasing rate. This is supported by the following non-exhaustive examples on CHO 'omics studies: genomics (Lewis et al, 2013;Xu et al, 2011), transcriptomics (Becker et al, 2011;Doolan et al, 2008), translatomics (Courtes et al, 2013), proteomics (BaycinHizal et al, 2012;Carlage et al, 2009), metabolomics (Selvarasu et al, 2012;Zang et al, 2011) and integrative 'omics (Clarke et al, 2012). Moreover, a consensus genome-scale reconstruction of…”
Section: Concluding Remarks and Future Directionsmentioning
confidence: 96%
“…Indeed, as recently stated by Clarke and Lee (2014), the CHO community is currently generating 'omics data at an ever-increasing rate. This is supported by the following non-exhaustive examples on CHO 'omics studies: genomics (Lewis et al, 2013;Xu et al, 2011), transcriptomics (Becker et al, 2011;Doolan et al, 2008), translatomics (Courtes et al, 2013), proteomics (BaycinHizal et al, 2012;Carlage et al, 2009), metabolomics (Selvarasu et al, 2012;Zang et al, 2011) and integrative 'omics (Clarke et al, 2012). Moreover, a consensus genome-scale reconstruction of…”
Section: Concluding Remarks and Future Directionsmentioning
confidence: 96%
“…In fact, Clarke et al 2011 found a set of 287 genes for the prediction of cellular productivity in the model they established. However, as this study was based on an early microarray chip that contained only ~3500 expressed CHO genes out of the estimated 15 000 transcripts present in a cell at any time [9], it is likely that many more mRNAs and other factors like non-coding RNAs (ncRNAs) play a role in determining productivity [10].…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive study of these genes in recombinant CHO cells is essential for a better understanding of the pathway and its response. Majority of existing studies are limited to a few chosen genes from these pathways and to few time-points (Murphy et al 2001;Underhill et al 2005;Cudna and Dickson 2006;Doolan et al 2008;Ku et al 2008). In this work, we undertake dynamic profiling of all major ER chaperones and UPR pathway genes in a batch culture.…”
Section: Introductionmentioning
confidence: 99%